IMPLEMENTATION OF QUALITY CONTROL TOOLS IN CONFECTION MYPES AND CONTINUOUS IMPROVEMENT PDCA APPLICATION - Pérez Gao Montoya, María (2017)
This article is about a company dedicated to export cloths, which outsource the process from the tissue to the garment finishing. The topic is centered in confections outsourcing, what is a MyPE and their problem respect to quality.Confections MyPEs do not count with a defined quality system, reason why the implementation of quality tools and continuous improvement to enhance their products (garment) quality standards is proposed. To implement this concept, the MyPE’s staff was trained to use quality control tools, continuous improvement tools and the auto control method. Measurements pre and post the implementation of the mentioned tools were taken. A reduction of the confection error rate of the MyPE was achieved.